Professional identification, perspective taking and the internal selection process for innovation - MACK, Daniel Z. (Institutional Knowledge at Singapore Management University, 2016)
In this conceptual paper, we contend that one of the factors that gives rise to the challenges of maintaining a sustainable internal selection environment is the different structural roles that top and middle managers enact in the innovation process. We propose that the extent to which the differences between the structurally differentiated role of top and middle managers could be reconciled harmoniously and integrated is dependent on the organization values embraced by the organization. In particular, we argue that two necessary dimensions are key to sustaining a viable internal selection environment for strategic innovation development: professional identification and perspective taking. We present a model of the interactions between top managers and middle managers in the innovation process, and theorize how a corporate culture that emphasizes both professional identification and perspective taking among employees can lead to behaviors supporting an enactment of a viable internal selection environment that produces value-creating strategic innovations. Our model also explains why certain dysfunctional internal selection processes emerge, which can lead to innovation underperformance.